MANAGEMENT OF FACILITIES AND INFRASTRUCTURE IN ISLAMIC EDUCATIONAL INSTITUTIONS - Ali Hajjaj, Wafi (International Conference on Humanity Education and Society (ICHES), 2025)
To create a comfortable, effective, and efficient teaching and learning environment, the learning process must be supported by facilities and infrastructure that meet the standards set by the government. With such provisions in place, the learning activities will produce high-quality outcomes, as they are supported by comprehensive educational resources.The availability of complete facilities can encourage students to develop their inner potential and compete confidently with others. Moreover, a well-equipped learning environment fosters a more dynamic atmosphere, in which students become more active and enthusiastic—even in the face of challenging material, they remain highly motivated to learn. This situation stands in stark contrast to classrooms lacking such facilities, where students tend to be less engaged and enthusiastic, resulting in confusion and difficulty in understanding the lessons. Educational facilities and infrastructure within an institution significantly influence the quality of education. Comfortable classrooms, well-equipped laboratories, and complete teaching aids play an active role in the learning process. Practical sessions conducted by students tend to yield better learning outcomes, as hands-on experiences in practice rooms contribute to the broadening of their knowledge and understanding. Educational facilities and infrastructure within an institution significantly influence the quality of education. Comfortable classrooms, well-equipped laboratories, and complete teaching aids play an active role in the learning process. Practical sessions conducted by students tend to yield better learning outcomes, as hands-on experiences in practice rooms contribute to the broadening of their knowledge and understanding.